Bridging Culture, Islamic Values, and Mathematics: Learning Geometry Concepts through the Great Mosque of Madaniyah Karanganyar - Hery Nugroho; Sugiman Sugiman (Tarbiyah : Jurnal Ilmiah Kependidikan, 2026)
Ethnomathematical studies in Indonesia have widely explored the presence of geometric concepts embedded in Muslim worship buildings, particularly mosques. These studies highlight how architectural structures and ornamental patterns reflect mathematical ideas rooted in cultural practices. Therefore, the research aims to explore and explain the geometric concepts in the buildings and ornaments of the Great Mosque of Madaniyah Karanganyar. This research employ ethnography as an approach to answer four main questions, namely "Where do I start looking?", "How do I find it?", "How do I recognize that it has found something significant?" and "How to understand what it is?". Data were collected through observations, semi-structured interviews, and documentation. Based on these four questions, the researchers successfully uncovered the geometric concepts contained in the buildings and ornaments of the Great Mosque of Madaniyah Karanganyar. The study's results stated that there are three concepts of geometry: 2D Geometry, 3D Geometry, and Geometric Transformation, which have been confirmed by geometric experts. It is hoped that these findings can be used to maintain mosque buildings and ornaments, as well as serve as a starting point for learning contextual and meaningful geometry.